2009
DOI: 10.1002/app.30635
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a silicone resin with silphenylene units in Si‐O‐Si backbones

Abstract: A silicone resin with silphenylene units in Si-O-Si backbones was synthesized by hydrolysis-polycondensation of 1,4-bis(hydroxydimethylsilyl)benzene (BHB) with chlorosilanes. The structure and property of this novel silicone resin were characterized by gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), thermogarvimetric analysis (TG), scanning electron microscope (SEM), and electrochemical impedance spectrum (EIS). This silicone resin could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…3 shows the TG and DTG curves of the silicone resin from room temperature to 900 • C under nitrogen atmosphere. The stability of this silicone resin was comparable with the reported ones [13]. It indicated that the synthesized silicone resin had good thermal stability.…”
Section: Thermal Degradation Of Silicone Resin Containing Silphenylensupporting
confidence: 81%
See 1 more Smart Citation
“…3 shows the TG and DTG curves of the silicone resin from room temperature to 900 • C under nitrogen atmosphere. The stability of this silicone resin was comparable with the reported ones [13]. It indicated that the synthesized silicone resin had good thermal stability.…”
Section: Thermal Degradation Of Silicone Resin Containing Silphenylensupporting
confidence: 81%
“…Little attention has been paid to change the structure of silicone resins in this way. Jia et al [13] synthesized silicone resins with silphenylene units by the reaction of 1,4-bis(hydroxydimethylsiyl)benzene with the hydrolysis products of chlorosilanes. Results showed that the synthesized silicone resins had good thermal stability, corrosion resistance and irradiation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The yellow filtrate was distilled under vacuum, and the product was collected at 170-180 C (2.0 kPa) to provide 36.0 g of 1,4bis(diethoxymethylsilyl)benzene (70%). 1 Preparation of Phenylene-Silica Sol TEOS and 1,4-bis(diethoxymethylsilyl)benzene (0.050 mol in total), hexamethyldisiloxane were mixed in a tetra-necked 100 mL round-bottomed flask with a dropping funnel, a condenser, a thermometer and a mechanical stirrer. The mixture was immersed into water bath of 15-20 C. Sulfuric acid (0.125 g, 1.25 mmol) was slowly dropped to the flask within 20 s. Deionized water (1.80 g, 0.100 mol) was fitted in dropping funnel, and was introduced into the reaction mixture within 20 min, while the temperature of the reactants was maintained below 20 C. Then the reaction mixture was heated to 78 C, stirred for 2.5 h. The system was neutralized by excessive amount of NaHCO 3 (0.500 g).…”
Section: Preparation Of 14-bis(diethoxymethylsilyl)benzenementioning
confidence: 99%
“…Two approaches have generally been used to improve the thermal stability of organosilicone polymer. One way is that the polymer chains could incorporate some rigid groups, such as arylene,1 carborane cage,2 or some larger rigid groups,3–5 which produce huge steric hindrance to transfer the conformations in case of decomposition caused by molecular thermal motion, and lead to an improved performance on thermal stability compared with pure SiOSi chains. Although these silicon‐containing polymers can resist sufficient high temperature up to 500°C, complicated synthesis procedures and high cost of monomers and polymers hampered their general applications.…”
Section: Introductionmentioning
confidence: 99%
“…Addition curable silicone resins are known to be cross‐linked semi‐inorganic polymers with the Si‐O‐Si chains as backbones and some organic groups as side chains, which possess combined properties of both organic and inorganic materials, such as low dielectric constant and loss, good resistance to heat, solvents, weathering, and radiation [1–3]. In addition, some addition curable silicone resins can be designed without solvents, and thus meeting some special fields, such as nonsolvent impregnation varnish, nonsolvent moulding compounds, and so on.…”
Section: Introductionmentioning
confidence: 99%